Intercellular delivery of bioorthogonal chemical receptors for enhanced tumor targeting and penetration. (November 2020) - Tu, Yalan; Dong, Yansong; Wang, Kewei; Shen, Song; Yuan, Youyong; Wang, Jun
Abstract: Targeted drug delivery using biological ligands can improve the precision of cancer therapy. However, this active targeting strategy is limited in tumor targeting and penetration abilities due to the paucity and heterogeneous distribution of targeted receptors in tumor cells, thus compromising the treatment outcomes. In this study, we developed an alternative active targeting strategy for enhanced tumor targeting and penetration through synthetic nanoparticle-mediated metabolic tumor ligand labeling for intercellular delivery of bioorthogonal chemical receptors combined with in vivo bioorthogonal click chemistry. Briefly, artificial azide-containing ligands were first labeled on perivascular tumor cells by nanoscale metabolic precursors (Az-NPs) via the enhanced permeability and retention (EPR) effect and metabolic engineering of the tumor cells. Through transport by extracellular vesicles (EVs) secreted by perivascular tumor cells, the azide-containing ligands can be autonomously transported intercellularly to adjacent cells and further spread throughout tumor tissues and label bioorthogonal ligands on cells that are not in proximity to blood vessels. Then, water-soluble dibenzocyclooctyne-modified chlorin e6 (DBCO-Ce6) was intravenously injected to react selectively, efficiently and irreversibly with the azide groups on the cell surface through an in vivo bioorthogonal click reaction. Enhanced tumor accumulation and penetration of DBCO-Ce6 was achieved through this strategy, resulting in improved therapeutic efficiency with laser irradiation for photodynamic therapy. Therefore, the artificial azide-containing ligand targeting strategy by nanoparticle-mediated metabolic labeling through the EPR effect combined with bioorthogonal click chemistry may provide an alternative strategy for enhanced tumor targeting and penetration with broad applications. Graphical abstract: Image 1